GAMBARAN EEG DAN RESPONS AWAL YANG BAIK TERHADAP OBAT ANTIEPILEPSI - Nurcahaya Sinaga (LP2MTBM MAKARIOZ, 2018)
Background. Epilepsy is one of neurological disorder that cause disability and death. Initial response to antiepileptic drugs (AEDs) is the best predictive indicator to determine remission of epilepsy. Electroencephalography (EEG) findings can help determine the type of epilepsy and the best choice of antiepileptic drug to be given. Objectives. To investigate how is response in monotherapy antiepileptic drug in patients with newly diagnosed epilepsy Method. Cohort prospective study was conducted by the looking the eeg findings in neurology outpatient clinic Cipto Mangunkusumo hospitals (RSCM) between January to August 2017 on newly diagnosed pediatric epilepsy. Response of AED monotherapy was observed after three months of treatment. Results. There were 92 subjects that fulfilled the criteria. The incidence of newly diagnosed epilepsy children at RSCM was 21.9%. Initial respons to monotherapy AED are 77,2% and electroencephalography (EEG) findings were normal 57,6% dan abnormal 42.4% to monotherapy AED in newly diagnosed epilepsy patient. Conclusion. Most of the subject have a good initial response to monotherapy AED. The influence factors of the initial response is EEG findings.